جدلية العولمة والإعلام في الفكر السياسي المعاصر ((أطروحة موت الواقع عند جان بودريار نموذجا)) - الفارسي أ.يوسف عبدالكريم محمد; اللواج أ. عزالدين عبدالعاطي (المجلة الدولية لعلوم الإعلام والاتصال, 2024)
ملخص الدراسة:- إن المشهد الإعلامي أنتقل اليوم في ظل العولمة من عصر الحقيقة إلى عصر الفضاء الإلكتروني. ونجد أثناء هذا التحول، يتم فيه قلب الواقع بأشكال وصور مزيفة. بعد أن كانت في السابق صورة الواقع، أصبحت الأن أمام واقع الصورة، فالحرب مثلا، باعتبارها واقعا. يتم الأن توظيفها إعلاميا، باعتبارها في وقت معين حدث تاريخي في منطقة جغرافية محددة ويتم تداول كل تفاصيلها دون نقص أو إضافة، وإنما يتم إخضاع صورة الواقع لكل عمليات التنقيح والتعديل والنقص والإضافة، بما يخدم مصالح الفئة المسيطرة على وسائل الإعلام. هذا يعني أن الصورة الإعلامية تلعب دور المخادع والمراوغ، وفرض واقع غير الواقع الموجود. الكلمات المفتاحية:- جدلية العولمة والإعلام، الفكر السياسي المعاصر، أطروحة موت الواقع، جان بودريار، تداعيات العولمة. Abstract: Study Summary:- Today, the media landscape has moved from the age of truth to the age of cyberspace. And we find during this transformation, reality is overturned in false forms and images. After it was previously an image of reality, it is now in front of the reality of the image, war for example, as it is a reality. It is now employed in the media, considering it at a specific time a historical event in a specific geographical area, and all its details are discussed without deficiency or addition, but the image of reality is subjected to all processes of revision, amendment, deficiency and addition, in a way that serves the interests of the group that controls the media. This means that the media image plays the role of deceiver and deceiver, imposing a reality other than the existing one . Key words :- The dialectic of globalization and the media, contemporary political thought, the thesis of the death of reality, Jean Baudrillard, and the repercussions of globalization.